On the provision of quality-of-service guarantees for input queued switches. - Nong, G. (IEEE Communications magazine)
While the Internet has quietly served as a research and education vehicle for more than two decades, the last few years have witnessed its tremendous growth and its great potential for providing a wide variety of services. As a result, input-queued switching architectures, because of their distinguished advantage in building scalable switches, are currently receiving a lot of attention from both academia and industry as an attractive alternative for developing future-generation ATM/IP switches/routers. However, the problem of designing scheduling algorithms with QoS guarantees for input-queued switches has always been known to be a very challenging problem. We give an overview of the efforts in designing scheduling algorithms capable of providing QoS guarantees for input-queued switches. These algorithms are classified under three categories: those based on slot time assignment, those based on maximal matching, and those based on stable matching. We also present some open problems on this topic as future research directions in this area.